Efficient modal-based method for analyzing nonlinear aerostatic stability of long-span bridges. (1st October 2021) - Cid Montoya, M.; Hernández, S.; Kareem, A.; Nieto, F.
Highlights: A novel aerostatic stability analysis method using a modal formulation is presented. Convergence to the critical wind velocity is accelerated through a root-finding algorithm in the outer loop. The proposed method is applied to a cable-stayed bridge considering multiple nonlinear features. The collapse is driven by stiffness degradation due to stays loss of tension and ultimately stiffness. The influence of aerodynamic and structural nonlinear features on the critical wind velocity is investigated. Abstract: An efficient method for analyzing the nonlinear aerostatic stability of long-span bridges using a modal formulation is proposed. First, a simplified linear version defined as modal-based approach is introduced, which evaluates the bridge displacements using the modal properties of the bridge and speeds up the assessment of the critical velocity by applying a root-finding algorithm. Then, this scheme is further developed to identify the instability limit point in nonlinear structures by combining nonlinear FEM analyses with the linear version of the modal-based approach and a root-finding algorithm in an outer loop. The effects of considering the three components of the wind loads, the stays sag effect, structural nonlinearities, aerodynamic nonlinearities, and the initial wind angle of attack, are analyzed and discussed. The computational advantages of the proposed method and its accuracy are demonstrated through three application examples, including a simplified linear 1 DoF system, and linear and nonlinear FEM models of a full cable-stayed bridge. The collapse mechanism of the cable-stayed bridge is driven by the stiffness degradation of the stays caused by the deck vertical upward displacements. It has been found that the influence of the nonlinear aerodynamic features is very low when the structural nonlinearities control the bridge collapse.